A New Evaluation: The Theological Influence of F. D. Maurice on the Imaginative Works of Lewis Carroll. - Gardiner, Karen (2023)
This thesis will explore how the fictional work of Lewis Carroll was influenced by mid nineteenth century eschatological ideas and controversies, particularly in relation to how eternity was understood and explored by F.D. Maurice and other Broad Church theologians who were friends and acquaintances of Carroll. As such, it is inevitably interdisciplinary in nature covering aspects of theology, Church history and Carrollian studies, and this is reflected in the bibliography. It will be argued that despite the plethora of biographical and literary works on Carroll, the theological aspects of the author’s work have been under researched. Thus, the limited secondary (theological) material available means that this thesis has been significantly guided by the primary sources of the works and letters of Maurice and his contemporaries (including letters to Carroll that have not previously been published in their entirety). It is argued that a deeper consideration of Carroll’s theological influences is a necessary element in understanding Carroll’s works more fully, and that this thesis could inform further study on how the Broad Church eschatology of Maurice may survive most fully not through his own books and sermons, but in the popular imagination through the fictional fantasy writing he inspired in his contemporaries such as Carroll, Kingsley and MacDonald (whose works are considered alongside Carroll’s in one of the chapters of this thesis). Maurice’s eschatology, and its presence in these fictional works, is considered in relation to his understanding of justice, freewill and predestination, Broad Church philology and the relationship between eternity, space and time. The place of dreams and the idealized child in eschatological understanding will also be explored. It is hoped that this thesis will help to broaden the scope of Carrollian studies to consider more fully theological influences in his writing, and that it may have the potential to pave the way for further consideration of the importance of Broad Church theology in the development of British fantasy fiction.